Development of PBL-Based Smart Apps Creator Media to Improve Science Learning Outcomes for Grade IV Elementary School Students - Nora Rizkiah; Sri Sami Asih (Postgraduate, University of Mataram, 2025)
The use of interactive learning models and media that are not optimal in the science learning process has a negative impact on student learning outcomes. Therefore, a solution is needed to overcome these obstacles, so this study aims to develop, test the feasibility, and effectiveness of learning media in improving the learning outcomes of fourth grade students. The resulting learning media is a smart apps creator based on Problem Based Learning (PBL) about the state of matter and its transformation. The research methodology with Research and Development (RnD) using the ADDIE paradigm includes analysis, design, development, implementation, and evaluation. A total of 27 fourth grade students of SD Negeri 2 Bojongsari participated in this study. The t-test showed a significant difference between the pretest and posttest results with a significance level of 0.00 meaning less than 0.05. The N-gain test shows moderate criteria with a score of 0.55 on a small scale and 0.62 on a large scale. The results of the study indicate that the smart apps creator learning media based on problem-based learning on the material of the state of matter and its changes has been successfully developed and is very feasible and effective in improving the learning outcomes of fourth grade students of SD Negeri 2 Bojongsari.